A foreign aid dilemma - Eskhult, Gustaf; Molin, Erik (2011)
Foreign aid is a very debated and controversial topic. The most recent studies have focused more on GDP growth and foreign aid correlation, however not much of the debate has focused on what kind of foreign aid should be given. The most common foreign aid is budget support, often a bilateral funds transfer between two countries. This kind of foreign aid can be both conditional and unconditional from the donors’ perspective. The most known type of foreign aid is project aid, often headed by a international organization, that see the entire project through, from raising funds, to actually be in the aid receiving country, establishing healthcare, education, road-construction etc.